UJI BEBERAPA KONSENTRASI TEPUNG DAUN BABADOTAN (Ageratum conyzoides L.) UNTUK MENGENDALIKAN HAMA KUMBANG BIJI KACANG HIJAU (Callosobruchus chinensis L.) DI PENYIMPANAN - Adhytia Ika Pramesty; Desita Salbiah (UIR Press, 2022)
Callosobruchus chinensis L. is a pest that can damage and reduce the quality of mung bean seeds in storage. Pest control can be done using botanical insecticide babadotan plants (Ageratum conyzoidez L.). This research aims to obtain an effective concentration of babadotan leaf flour against C. chinensis in storage. The research was conducted at the Plant Pest Laboratory, Faculty of Agriculture, University of Riau. The research used a completely randomized design (CRD) with six treatments and four replications. The treatments were given several concentrations of babadotan leaf flour 5 g.100 g-1, 6 g.100 g-1, 7 g.100 g-1, 8 g.100 g-1, 9 g.100 g-1 dan 10 g.100 g-1 mung bean seeds. The parameters observed were an initial time of death, Lethal time 50, daily mortality, total mortality, individual increase, and weight loss of seeds. The results showed that the concentration of babadotan leaf flour 9 g.100 g-1 mung bean seeds was effective to control C. chinensis because it could cause total mortality at 87.50% with an initial time of death of 7.50 hours after application and Lethal time of 50 of 33.75 hours after application and resulted in an increase of 5.50 individuals and was lead to a weight loss percentage of mung beans seeds by 0,70%.